2015
DOI: 10.1098/rsos.140535
|View full text |Cite
|
Sign up to set email alerts
|

Uncomfortable images produce non-sparse responses in a model of primary visual cortex

Abstract: The processing of visual information by the nervous system requires significant metabolic resources. To minimize the energy needed, our visual system appears to be optimized to encode typical natural images as efficiently as possible. One consequence of this is that some atypical images will produce inefficient, non-optimal responses. Here, we show that images that are reported to be uncomfortable to view, and that can trigger migraine attacks and epileptic seizures, produce relatively non-sparse responses in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 34 publications
4
36
0
Order By: Relevance
“…Individuals who are particularly susceptible to discomfort exhibit an abnormally large haemodynamic response 8, 9. The large haemodynamic response is consistent with neural models that show a larger neural response to these stimuli, one in which the sparseness of firing within the network is reduced, suggesting an inefficient cortical processing of uncomfortable stimuli 10 . This interpretation is in turn consistent with evidence that the mathematical properties of uncomfortable stimuli differ from those of natural scenes 11, 12, 13, 14.…”
Section: Introductionsupporting
confidence: 83%
“…Individuals who are particularly susceptible to discomfort exhibit an abnormally large haemodynamic response 8, 9. The large haemodynamic response is consistent with neural models that show a larger neural response to these stimuli, one in which the sparseness of firing within the network is reduced, suggesting an inefficient cortical processing of uncomfortable stimuli 10 . This interpretation is in turn consistent with evidence that the mathematical properties of uncomfortable stimuli differ from those of natural scenes 11, 12, 13, 14.…”
Section: Introductionsupporting
confidence: 83%
“…It is also consistent with the findings that higher contrast patterns are more uncomfortable (Haigh, Cooper, and Wilkins, 2014) and the associations between migraine and neural activity in primary visual cortex (Huang et al, 2003). This account would predict that 1/ f spectra should produce weaker or more efficient neural responses, and as noted this has been predicted in computational models (Hibbard and O’Hare, 2015). Surprisingly however, two recent fMRI studies have instead found stronger BOLD responses for 1/ f patterns compared to steeper or shallower spectra, albeit for patterns with moderate contrast of 30% (Isherwood, Schira, and Spehar, 2017; Tregillus et al, 2014).…”
Section: Discussionmentioning
confidence: 63%
“…The discomfort from unnatural images might therefore result because they lead to inefficient coding or overstimulation (Fernandez and Wilkins, 2008; Juricevic et al, 2010). Consistent with this, Hibbard and O’Hare (2015) and Penacchio et al (2015) used computational models of primary visual cortex (V1) and showed that uncomfortable images which do not contain the 1/ f structure lead to a non-sparse distribution of neural firing.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…9 The defining characteristic of this sparse response is that few neurons are active while many are inactive, thereby reducing metabolic demand. Hibbard and O'Hare 10 have used a computational model of visual area V1 to show that uncomfortable stimuli such as striped patterns, which are rare in nature and do not conform to a 1/f structure, result in an excess of 'neural activity' and a non-sparse distribution of 'neural' firing.…”
Section: Neural Computationmentioning
confidence: 99%